Computational insights into the reactivity for the [2+5] cycloaddition reactions of norbornene-linked group 14 element/P-based and Si/group 15 element-based frustrated Lewis pairs with benzaldehyde - Zhang, Zheng-Feng; Su, Ming-Der (Physical chemistry chemical physics : PCCP, 2023)
The element effects of Lewis acid (LA) and Lewis base (LB) on the potential energy surfaces of [2+5] cycloaddition reactions of norbornene-based G14/P-based (G14 = group 14 element) and Si/G15-based (G15 = group 14 element) frustrated Lewis pair (FLP)-type molecules with benzaldehyde were theoretically examined via density functional theory and several sophisticated methods. The theoretical findings indicated that among the above nine norbornene-linked G14/G15-based FLPs, only the Si/N-Rea , Si/P-Rea , and Si/As-Rea FLP-assisted compounds can readily undergo cycloaddition reactions with doubly bonded organic systems from kinetic and thermodynamic viewpoints. The energy decomposition analysis showed that the bonding interactions between the norbornene-based G14/G15-FLPs and benzaldehyde are better described in terms of the singlet-singlet model (donor-acceptor model) rather than the triplet-triplet model (electron-sharing model). In particular, natural orbitals for chemical valence findings revealed that the forward bonding is the lone pair (G15) → p-π*(C) interaction, which is a significantly strong FLP-to-benzaldehyde interaction. However, the back-bonding is the p-π*(G14) ← lone-pair orbital(O) interaction, which is a weak benzaldehyde-to-FLP interaction. The analyses based on the activation strain model showed that the larger the atomic radius of either the G14(LA) or the G15(LB) atom, the greater the G14 G15 separation distance in the norbornene-based G14/G15-FLP molecule, the smaller the orbital overlaps between G14/G15-FLP and Ph(H)C&z.dbd;O, and the higher the activation barrier during its cycloaddition reaction with benzaldehyde. Only Si/P-based, Si/N-based, and Si/As-based FLPs can facilitate the [2+5] cycloaddition reaction with benzaldehyde both kinetically and thermodynamically.